The Hazards of Making Constitutions: Some Reflections on Comparative Constitutional Law - Palmer, Sir Geoffrey (Victoria University of Wellington Law Review, 2002)
After teaching comparative constitutional law in the United States, Sir Geoffrey Palmer explores the nature of constitutional law in general terms and how New Zealand could learn from others. The author compares New Zealand's uncodified constitution to, for example, the United States who has a codified written constitution. The article then discusses the entrenched nature of some constitutions, compared to New Zealand's flexible and fluid constitution that exists largely in several ordinary statutes. Because of New Zealand's fragmented constitution, it is argued that its constitution has an unclear and indeterminate status; indeed, constitutional policy hardly makes an appearance in New Zealand politics. The author briefly looks at how constitutions protect fundamental rights and constitutional design in general terms, concluding that New Zealand's discussions on constitutional themes are too infused with analytical positivism, legalism, and traditionalism for policy issues. Finally, the author discusses the role of Fiji's constitution in light of its military coups. The author concludes that constitutional reform is needed in New Zealand in the form of a written and codified constitution.